Konsep Keadilan Harga Perspektif Ekonomi Islam - Fadly Yashari Soumena; Ihsan Nuari Imran; Tertia Salsabila (Institut Agama Islam Sumatera Barat, 2024)
The study aims to examine more deeply the urgency of price-setting justice from an Islamic perspective. The study uses a library-based research method that analyzes sources of previous scientific literature. Through a review of previous literature, the study analyzes the role of prices, the purpose of pricing, and the method for pricing. In Islamic economic perspectives, prices are seen as the result of the interaction of supply and demand in markets governed by Islamic ethical principles. The concept of righteousness in Islam not only con-siders the aspect of profit but also takes into account the value of justice and morality. Islamic ethical principles also teach that economic actors should avoid exploitation and fraud in pricing. All forms of practices that are detrimental to others, such as monopolies and price manipulation, as well as stockpiling goods to become rare, are also prohibited in Islamic teachings. In Islam, it is affirmed that the owner of goods or services should not seek excessive profits or harm consumption. The principle of fairness guides the determination of prices that correspond to the intrinsic value of the goods or services offered, as well as paying attention to the purchasing power of the public. In this regard, prices should reflect moral and social values and not contradict the principles of justice and social balance. By developing the concept of price in Islamic eco-nomics, it is important to ensure that moral values and justice are embodied in every aspect of economic activity. Thus, Islamic economics provides a holistic view that takes into account the material and spiritual aspects of achieving the well-being of society in its entirety.